Evaluation of Lower Limb Neuromuscular System Observability and Estimability of Muscle Activity. Issue 4 (3rd July 2020) - Song, Hyungeun; Hori, Yoichi
Abstract: In this work, we describe a method for estimating the muscle activity without drawing any assumptions regarding optimality principles in human motor control strategies; further, the method does not require any neural circuitry modeling which limits the neurophysiological terms and estimability of the method. We introduce the concept of system observability, which can reconstruct states from outputs and their derivatives based on system dynamics. Based on neuromuscular system observability, we estimate the muscle activity from joint torques and kinematics of multiple locomotive gaits, while considering the unknown neural inputs as system disturbances. Moreover, to quantify the robustness of the method, the degree of observability and parameter sensitivity are evaluated. Finally, the neurophysiological implications and generality of the method are addressed.